The Prevalence of Multiple Sclerosis in 3 US Communities - Curtis W. Noonan, PhD; Dhelia M. Williamson, PhD; Judy P. Henry, PhD; Robert Indian, MPH; Sharon G. Lynch, MD; John S. Neuberger, DrPH; Randolph Schiffer, MD; Janine Trottier; Laurie Wagner; Ruth Ann Marrie, MD, PhD (Preventing Chronic Disease, 2010)
IntroductionWe estimated the prevalence of multiple sclerosis (MS) in 3 large geographic areas in the southern, middle, and northern United States.MethodsThe primary data source was medical records from office visits to private neurologists’ practices or to neurology departments in tertiary care facilities during a 3-year period. Additional data sources included patient advocacy groups, nursing homes, and general practitioners.ResultsThree-year US age-adjusted prevalence estimates for the study areas varied substantially. The prevalence was lowest (47.2 per 100,000 population) in the Texas study area (33°30′ north latitude), intermediate (86.3 per 100,000 population) in the Missouri study area (39°07′ north latitude), and highest (109.5 per 100,000 population) in the Ohio study area (41°24′ north latitude). The geographic differences remained strong after age-adjustment to the world standard population. The inverse association between UV light exposure and MS prevalence estimates was consistent with this observed latitude gradient. In all 3 areas, MS prevalence was highest among women, people aged 40 to 59 years, and non-Hispanics.ConclusionThese results provide necessary prevalence estimates for community cluster investigations and establish baseline estimates for future studies to evaluate temporal trends in disease prevalence.